Hemodynamic Effects of 0.375% versus 0.25% Bupivacaine During Cervical Epidural Anesthesia for Hand Surgery. Issue 1 (January 1995) - Biboulet, Philippe; Deschodt, Jacques; Capdevila, Xavier; Landreau, Liliane; Aubas, Pierre; du Cailar, Jacques; d'Athis, Françoise
Abstract : Background and Objectives: Cervical epidural anesthesia with 0.375% or 0.25% bupivacaine plus fentanyl is a reliable technique for surgical restoration of digital motionafter tourniquet release and rehabilitation. The study was designed to assess the hemodynamic effects of this technique in 11 ASA 1 patients. Methods: The epidural catheter was introduced at the C7-T1 interspace on the day of operation. The volume of 0.375% bupivacaine necessary to block the brachial dermatomes was determined. The day after (day 1), every patient received epidurally the determined volume of 0.375% bupivacaine plus 1 μ g/kg fentanyl (group A). On day 2 the same volume of 0.25% bupivacaine plus 1 μ g/kg fentanyl (group B) was injected. For each patient one or several pairs of injection (A + B) were performed in relation with duration of rehabilitation. Cardiac index, stroke volume index, end diastolic index, ejection fraction, and systemic vascular resistance were studied by thoracic electrical bioimpedance. These parameters, mean arterial pressure and heart rate were recorded before and after injection. Sensory level was assessed by loss of cold sensation. Results: Nineteen paired injections were performed. Mean volume of bupivacaine was 7.1 ± 2 mL. The caudad sensory level was lower in group A: T7 (T3-L1) versus T6 (T2-T11) in group B. Hemodynamic variables were not different between the 2 groups. Mean arterial pressure cardiac index, heart rate, stroke volume index, and ejection fracture decreased slightly as end diastolic index remained unchanged and systemic vascular resistance increased slightly. No correlation was found between hemodynamic changes and spread of analgesia. Conclusions: Hemodynamic effects, in ASA 1 patients, are moderate and not dependent on the studied concentration of bupivacaine, indicating that a similar degree of sympathetic block is achieved with 0.375% and 0.25% bupivacaine.